Penerapan Pembelajaran Matematika Interaktif Berbasis Teknologi Untuk Menghubungkan Konsep Akademik Dengan Kehidupan Digital Siswa - Faisal Sattar; Erwin Nurdiansyah; Nur Afni; Abdul Wahid (Science and Education Journal (SICEDU), 2026)
This study aimed to improve students’ mathematics learning outcomes through the implementation of technology-based interactive mathematics learning to connect academic concepts with students' digital lives at UPTD SD 88 Sabantarng, Tompobulu District, Maros Regency. This research employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were students of UPTD SD 88 Sabantarng in the 2025/2026 academic year. Data were collected through learning achievement tests, observations, and documentation. The results showed that technology-based interactive mathematics learning improved students' learning outcomes. The use of digital learning applications, interactive videos, and digital quizzes increased students' participation, enthusiasm, and understanding of mathematical concepts related to their digital lives. Learning mastery improved from the pre-cycle to cycle I and cycle II. Therefore, technology-based interactive mathematics learning effectively improved mathematics learning outcomes in elementary school students.